RECOGNITION OF ANTS IN LA MACARENA RESERVE - FERNÁNDEZ, FERNANDO; SCHNEIDER-S., LAURA (Revista Colombiana de Entomología, 1989)
Specimens of 6 subfamilies, 18 tribes, 37 genera, and 95 species were found an inventory of ant fauna of the northwestern region of the Reserva La Macarena (Meta, Colombia) between December 1986 and January 1987, was found these anís show broad behavior in nidification, dietary resources, plant associations, and mimicry models. This rich forms should be understanding at the intense speciation and expansion of this group in South America, since mid tertiary.